Development of a Wire-Driven Robotic Fish Based on Double Sine Mechanism - Qian Yang; Qixin Wang; Zihao Cao; Zeyue Zhao; Ye Chen; Yong Zhong (Biomimetics)
Wire-driven robotic fish can effectively simulate the movement of real fish, but research on high-frequency wire-driven robotic fish is limited. This paper introduces the development of wire-driven robotic fish based on a double-sine mechanism. The appearance of the fish body is designed based on the morphology of tuna, and a mechanism that can support the high-frequency movement of the wire-driven mechanism is designed. The swimming speed and turning performance of the robotic fish are experimentally tested at various swing frequencies. The experimental results show that within the range of 1 to 4 Hz, the swimming speed of the robotic fish with different tail stiffness increases as the frequency increases. However, when the frequency exceeds 4 Hz, the swimming speed decreases. The tail joint with lower stiffness performs better at low frequencies, but as frequency increases, higher stiffness results in better swimming performance. Experimental tests show that the turning radius increases with higher swing frequencies and lower stiffness, resulting in a larger turning radius. This experiment will help to improve the application of high-frequency wire-driven mechanisms in the study of robot fish movement and carry out more in-depth bionic research in the future.